Keberhasilan Acupressure dalam menurunkan Kadar Glukosa Darah Pasien DM Tipe 2 - Sumah, Dene Fries; Sofiani, Yani; Kamil, Abdu Rahim; Ohorella, Usman Barus (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Diabetes mellitus (DM) type 2, occurs due to the body's inability to respond to insulin activity produced by the pancreas (insulin resistance) so that normal glucose levels are not achieved in the blood. In response to the manifestations and complications of Type 2 DM, various pharmacological and nonpharmacological therapies are needed. One of the efforts of non-pharmacological therapy is Acupressure. Acupressure is a TCM method using noninvasive finger pressure on the meridians of the body. Acupressure can release endorphins in the brain to lower blood glucose levels. This study aims to prove the success of acupressure therapy in reducing blood glucose levels of DM Type 2 patients at Dr. M. Haulussy Ambon Hospital. The research design used is a quasi-experiment with a pre and post-test approach without control. The population of this study was Type 2 DM patients who underwent uncomplicated inpatient and outpatient treatment with 30 respondents and the sampling technique was simple random sampling. Data analysis using univariate, bivariate with independent t-test samples. The results of this study showed that the average value of respondents' blood glucose levels before and after acupressure per week decreased by 161.07 with a standard deviation of -8.98. This proves that there is a significant difference in values between glucose levels before the test and after the test in respondents with a statistical p-value test result of 0.002. This means that giving treatment in the form of acupressure to patients with Type 2 DM can cause a decrease in blood glucose levels.   Keywords: DM type 2; acupressure; blood glucose levels